Perceived differences in skating characteristics resulting from three cross sectional skate blade profiles - Kendall, M.; Foreman, S.; Rousseau, P.; Hoshizaki, B. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to document differences in perceived skating characteristics resulting from three unique cross sectional skate blade profiles. Sixteen (n=16) University level hockey players were used in this double blind study looking at the perceived performance differences of four different skate blade profiles. No significant differences were found between skate blade profiles, preferred skate blade profile and time to complete given drills. Future research should look at different blade profiles and their interaction at ice level.